2015
DOI: 10.1007/s00216-015-8738-7
|View full text |Cite
|
Sign up to set email alerts
|

In situ DRIFT, Raman, and XRF implementation in a multianalytical methodology to diagnose the impact suffered by built heritage in urban atmospheres

Abstract: This work addresses the evaluation of an innovative mutianalytical method to assess the conservation state of a fifteenth century palace house. With the goal of reducing the handicaps of field analysis, the in situ spectroscopic assessment, often based on the use of X-ray fluorescence and Raman spectrometers, was complemented by the use of diffuse reflectance infrared Fourier transform spectroscopy. In this manner, its usefulness as a diagnostic tool to discover the origin and mechanisms of the damage caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Focusing on the bibliography, aphthitalite and thenardite have the same principal Raman band at 993 cm −1 and the low part of the spectra is quite similar. However, even though the next most intense band in both cases appears at 452 cm −1 , previous studies of our research group have shown that the ratio between the 993 and 452 cm −1 bands was not the same in both compounds . Taking this into account, it was assumed that the area ratio could be a good starting point to obtain a reliable methodology to differentiate both spectra.…”
Section: Resultsmentioning
confidence: 89%
“…Focusing on the bibliography, aphthitalite and thenardite have the same principal Raman band at 993 cm −1 and the low part of the spectra is quite similar. However, even though the next most intense band in both cases appears at 452 cm −1 , previous studies of our research group have shown that the ratio between the 993 and 452 cm −1 bands was not the same in both compounds . Taking this into account, it was assumed that the area ratio could be a good starting point to obtain a reliable methodology to differentiate both spectra.…”
Section: Resultsmentioning
confidence: 89%
“…A decade ago, for example, a compact, potentially transportable prototype instrument capable of carrying out Raman, laser‐induced breakdown, and laser‐induced fluorescence spectroscopy using a single‐pulsed laser source was developed for the analysis of cultural heritage objects and successfully tested on ultramarine blue pigments and proteinaceous binders . To this seminal body of literature, one must add a handful of Raman studies carried out with the aid of movable instrumentation, which focus on the assessment of certain materials' conservation state or degradation processes, most notably building materials and outdoor steel sculptures . The performances of portable Raman instrumentation have been also compared with those of mobile Fourier‐transform infrared spectroscopy to monitor the conservation treatment of monument plaster surfaces using various classes of polymeric consolidants and protectives …”
Section: Introductionmentioning
confidence: 99%
“…In the Pompeii mural paintings, the formation of coquimbite on the surface is generated by the interaction of iron (III) oxide with carbonate and sulfate anions of the plaster generated by cycles of wet deposition of acid aerosol (SO 3 or H 2 SO 4 ) of the environment. As attested by Gomez et al the formation of iron sulfate in the pore stones can occur at pH values lower than 4.5 as occurs in the presence of acid pollutants. Subsequently, coquimbite is produced by hydration processes.…”
Section: Resultsmentioning
confidence: 99%